Pelaksanaan Otonomi Daerah Terhadap Pembangunan Masyarakat Di Kabupaten Indragiri Hulu - Rosmita Rosmita; Herman Herman (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
Regional autonomy is an authority granted by the central government to the lower level governments, namely the Provinces, Regencies / Cities to manage their own households. The purpose of this study was to determine the implementation of regional autonomy towards community development in Indragiri Hulu Regency. The usefulness of this research should be of theoretical, practical and academic benefit, of course. This type of research uses qualitative and quantitative research types that are descriptive based on the information the author obtained, through primary data and secondary data, with respondents totaling 200 people. The technique of analyzing the data the authors conducted a qualitative analysis that would be carried out through primary, secondary, and library sources. The analysis will use a descriptive approach. The results showed that the implementation of regional autonomy carried out by the Government of the Indragiri Hulu Regency in the category did not go well. But on the other hand, the deliberation of the development plan (Musrenbang) through the Regional Work Unit (SKPD) in the category is not running well with the policy of the City / Regency Government only prioritizing the local government and the central government. In addition, the effect of implementation on community development is not well categorized in the development of basic facilities, infrastructure.